Applicability of the SWAT Model in Medium-Sized River Basins of Nepal: A Case Study of East Rapti and Kankai River Basin - Shahi, Tekendra; Regmi, Ram Krishna; Neupane, Yogesh Sharma; Baniya, Rupesh (Journal of Advanced College of Engineering and Management, 2025)
Hydrological modeling in data-scarce regions faces challenges that hinder effective water resource planning. Adhering to these challenges, numerous ungauged or poorly monitored basins are present in Nepal, which need a suitable methodology to address these problems. This study examines the applicability of the SWAT model in medium-sized, rain-fed perennial river systems: the East Rapti and the Kankai River Basins. Using the SUFI-2 algorithm in SWAT-CUP, calibration was performed with thirty parameters based on observations at Rajaiya (East Rapti) and Mainachuli (Kankai) station. Results showed that SWAT could replicate the hydrological response at daily scale, except the high flow events. The model performed very well at monthly scale with NSE values ranging from 0.83 to 0.94, R² from 0.86 to 0.96, and PBIAS below 15%. In both river basins, the groundwater parameter (GWQMN) was found to be most sensitive. These findings support water resources availability assessment and resource management at basin-scale.